Regional differences in adolescent childbearing in Nigeria (2016)
Nigeria’s total fertility rate (TFR) and adolescent first birth rate are among the highest worldwide, but variation exists by region. Unfortunately, data to monitor the level of adolescent first births is still scarce in Nigeria. This study examines regional differences in the level of adolescent first birth among women ages 20-49 years (n=23,801) in Nigeria. Data were analyzed using Chi-square and Cox proportional hazard models (α=0.05). Mean age at first birth was lower in the regions of higher TFR, among less educated and poorer women. In the South East, as for other regions in Nigeria, the mean children ever born was 6.13±2.8, 5.18±2.8, 4.1±2.4 and 2.97±1.9 for women who had their first birth at ages <15, 15-19, 20-24 and ≥25 respectively. The adolescent first birth was highest in the North West (74.8%, TFR=6.7) and lowest in the South West (32.1%, TFR=4.6). The hazard-ratio of beginning first birth was 1.58 (CI=1.46-1.70), 2.87 (CI=2.68-3.07), 3.43 (CI=3.23-3.67) and 1.74 (CI=1.61-1.88) higher in the North Central, North East, North West and South South, respectively, than the South West. Regional differences exist in adolescent first birth in Nigeria and TFR was higher in the regions where adolescent first birth was prevalent. Improving women’s education, particularly in the core northern regions, can raise the age at first birth in Nigeria.